Development, structural and rheological characterization, and in vitro evaluation of the zinc-doped 45S5 bioactive glass-vaseline ointment for potential wound healing applications - Ozarslan, Ali Can; Ozel, Cem; Okumus, Melisa Dilara; Dogan, Dilsa; Yucel, Sevil (SPRINGER HEIDELBERG, 2023)
Bioactive glass (BG) has recently been proposed to be used for wound healing with Vaseline (R). To accelerate the wound healing by incorporation of the Zinc (Zn) into BG, undoped and 5 wt% zinc-doped 45S5 BG (16 wt%) were prepared with Vaseline (R) to create the ointments for wound healing as a VBG and VBG-Zn, respectively. The results showed that desired composition, irregular form, and no porous surface have obtained for BGs. FT-IR spectrum of Zn-doped BG demonstrates increasing Network Connectivity due to Zn incorporation. Ointments exhibited pseudoplastic behaviour and viscoelastic characteristic, indicating that ointments have good topical application. Ointments did not toxic effect towards L929 cells in terms of biocompatibility for topical applications. In vitro wound healing assays revealed that VBG-Zn promotes wound healing thanks to incorporation of the Zn accelerates skin wound closure. All findings point to VBG-Zn ointment having a greater potential for wound healing applications.
Keywords: Bioactive glass; Ointment; Vaseline; Wound healing; Zinc-doped; GEL-DERIVED GLASSES; SOL; NANOPARTICLES; CREAM; SKIN; CRYSTALLIZATION; ANGIOGENESIS; STRONTIUM; HYDROGELS; IONS; Materials Science